Tiga warna orientasi pendidikan akuntansi masa depan - Bonnie Soeherman (Akuntansi dan Teknologi Informasi, 2024)
The WEF 2020 report has disrupted the world of education and the accounting profession. The role of accounting, traditionally carried out by humans, is gradually being overshadowed by technology. The sustainability of this profession serves as the primary background for this research, along with the direction and orientation of the future development of the accounting discipline, questioning its continued relevance. This study aims to analyze the future development, challenges, and opportunities in accounting education. It also seeks to construct a conceptual model for the orientation of accounting education development that aligns with the times. The research results are expected to contribute to developing educational curricula and the accounting profession. This study employs an interpretive-constructive approach through literature review. This research's analysis, mapping, and interpretative processes revealed three orientations in the development of accounting education referred to as Red, Green, and Blue (RGB) Accounting. Each represents standardization, globalization, geopolitics, sustainability, and innovation and technology. These three colors, known as True Tone, are expected to strongly influence accounting practices and serve as a crucial reference in the development of accounting education curricula.